Impacts of outdoor and indoor air pollution on COVID-19 health outcomes and interventions in the Southern African development community region: a scoping review - Banwari, Aleya (Department of Public Health and Family Medicine, 2025)
Purpose of Review: The Southern African Development Community (SADC) faces high poverty and pollution levels, with nearly half of urban residents living in informal settlements. Research on air pollution's impact on COVID-19 in SADC is limited. This review explored how pollutants like fine particulate matter (PM₂.₅), nitrogen dioxide (NO₂), and household air pollutants (HAP) affect COVID-19 severity. We examined outdoor and indoor exposures, noting that solid fuels and poor ventilation increase respiratory risks in low-income communities. We identified key pollutants, proposed mitigation strategies, highlighted knowledge gaps, and made recommendations for air quality management during and after pandemics. Recent Findings: Of 331 studies, 19 met eligibility criteria, with 11 from SADC countries like South Africa, Zimbabwe, and Zambia. Findings indicate that prolonged exposure to PM₂.₅ and NO₂ harms lung function, worsens asthma and chronic obstructive pulmonary disease (COPD), and increases COVID-19 hospitalisations and mortality. In many SADC informal settlements, poorly built structures limit ventilation, and burning biomass and paraffin indoors increases pollutant levels. Lockdowns may have reduced outdoor pollution, but indoor pollution increased, particularly harming vulnerable groups. Limited data from rural and low-income areas hinders thorough assessments of pollution-related health risks and the creation of effective, tailored policies. Summary: The interplay of air pollution, socio-economic inequalities, and constrained healthcare capacity intensifies COVID-19 outcomes in the SADC region. To address these intertwined challenges, urgent cleaner energy transitions, enhanced air quality monitoring, and strategies to reduce household pollution are needed. Stronger local research will support evidence-based policymaking, strengthening public health and pandemic resilience.